Environmental Assessment of a Constructed Wetland with Ornamental Vegetation for Wastewater Treatment: A Sustainable Option for Neighborhoods (The Case of Veracruz, Mexico) - Sergio Aurelio Zamora-Castro; Humberto Raymundo González-Moreno; María Graciela Hernández-Orduña; Irma Zitácuaro-Contreras; José Luis Marín-Muñiz (World)
The discharge of wastewater into bodies of water and subsoil poses a serious pollution problem. In many neighborhoods or districts, there are often no wastewater treatment systems due to the high costs involved, which may compromise human health. Constructed wetlands (CWs) offer an ecological solution to improve water quality and enable its reuse. They promote the removal of contaminants through physical, chemical, and biological processes. The objective of this study was to evaluate Canna hybrids, Zingiber spectabile, and Alpinia purpurata—ornamental plants not typical of wetlands—regarding their function as phytoremediators and their growth under such conditions. Utilizing CWs with ornamental plants for water treatment in neighborhoods could improve the adoption of this ecotechnology. To this end, eight cells were built: two were controls (without plants), two contained Canna hybrids, two had Zingiber spectabile, and two included Alpinia purpurata, all designed for a hydraulic retention time of three days. Inlet and outlet water samples were collected biweekly for six months. The results showed that the cells with Canna hybrids and Zingiber spectabile removed from 40 to 70% of total nitrogen and phosphorus. In terms of organic matter, measured as COD and TSS, the removals ranged from 55 to 90%. In contrast, cells with Alpinia purpurata demonstrated removal rates of only 30 to 50%, which were statistically lower (p ≤ 0.05), indicating a slower adaptation to wetland conditions. This slower adaptability is directly related to the growth of the species, as Alpinia purpurata also exhibited the lowest growth rates. The study concluded that using CWs with the studied ornamental plants is a viable alternative for treating wastewater and, at the same time, they may add a commercial value to the vegetation. Additionally, they can enhance the aesthetic landscape with colorful flowers that attract birds and insects and the treated water could be utilized to irrigate sports areas or urban planters.